Features Of The Pathogenesis And Correction Of Anemia Induced By Antiviral Therapy For Hepatitis C - Ismatova Mekhriniso Nasritdinovna; Nurullaeva Dilnoza Fatullevna (The American Journal of Medical Sciences and Pharmaceutical Research, 2021)
HCV infection remains one of the leading problems in the diagnosis and treatment of chronic liver disease, given the scale of hepatitis C virus infection worldwide, the significant number of unexamined but at-risk patients, and the incidence of cirrhosis and liver cancer. Anemia is the most common hematological adverse event, which in turn significantly reduces the quality of life of patients during antiviral therapy, their adherence to treatment, and increases the risk of developing cardiovascular, renal and cerebral disorders.